1991
DOI: 10.1007/bf00856644
|View full text |Cite
|
Sign up to set email alerts
|

Microheterogeneity of urinary albumin and tubular proteinuria in juvenile diabetes mellitus

Abstract: We studied differential urinary albumin excretion by a double one-dimensional gel electrophoresis with decyl sodium sulphate-polyacrylamide gel electrophoresis in the first, and isoelectric focusing in the second dimension in 37 diabetic children and 20 healthy subjects. In addition, total proteins, albumin, beta 2-microglobulin and molecular size distribution of urinary proteins were measured, the latter using sodium dodecyl sulphate-polyacrylamide gel electrophoresis. Whilst albuminuria was not significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The data of the present study are in accordance with other researchers that reported a high frequency of qualitative differences in urine proteins (30) and a variety of electrophoretic patterns (15) in the urine of well controlled diabetic adolescents without microalbuminuria. These observations indicate that early stages of diabetic nephropathy may involve both glomerular and tubular dysfunction.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…The data of the present study are in accordance with other researchers that reported a high frequency of qualitative differences in urine proteins (30) and a variety of electrophoretic patterns (15) in the urine of well controlled diabetic adolescents without microalbuminuria. These observations indicate that early stages of diabetic nephropathy may involve both glomerular and tubular dysfunction.…”
Section: Discussionsupporting
confidence: 95%
“…Increased amounts of low molecular weight proteins in the urine of diabetic patients give evidence of decreased tubular reabsorbtion as an early sign of diabetic nephropathy (5,12,13,14,30). On the other hand increased permeability of the glomerular membrane (23,24) is expected to cause increased amounts of high molecular weight proteins in the urine of diabetic children.…”
Section: Discussionmentioning
confidence: 94%
“…Coomassie brilliant blue (Biorad) was used to measure total protein [15]. For determination of LMW and HMW proteins, we used sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) after concentration of the urine by dialysis [16,17]. We used 0.48-mm-thick slab gels with an exponential polyacrylamide gradient from 4.0% to 22.5%, according to Goerg et al [16], and the Laemmli buffer system.…”
Section: Methodsmentioning
confidence: 99%
“…An increase in the charge microheterogeneity of serum albumin -with an increase in the isoelectric point -has been described in adolescents with diabetes. 39 Cationization of albumin changes its spatial configuration 40 and may thus also influence its size-based exclusion by the capillary wall 39 or increase its binding to the negatively charged brush border of proximal tubule cells, thereby increasing its reabsorption. 41 Finally, albumin glycosylation cannot explain enhanced albuminuria in obese or hypertensive subjects with decreased insulin sensitivity, but no overt diabetes.…”
Section: Why Should Insulin Resistance Enhance Albuminuria?mentioning
confidence: 99%